Pemetaan Elemen Artificial Intelligence Sesuai Tiga Struktur Pertahanan: Operational, Tactical, Dan Strategic - Erika, Katherine; Supriyadi, Asep Adang; Ghazalie, Ghazalie; Djansena, Alradix (Jurnal Ilmiah Global Education, 2025)
This research analyzes the AI components Machine Learning, Neural Networks, Natural Language Processing, and Robotics and their allocation within Indonesia’s three-tiered defense structure: operational, tactical, and strategic. This paper explores the integration of Artificial Intelligence (AI) into Indonesia's national defense policy, examining opportunities, challenges, and strategic implications. AI's transformative potential spans operational efficiency, strategic decision-making, and robust cyber security. This research employs a qualitative approach, examining previously published scholarly articles across various journals to understand the multifaceted dimensions of Artificial Intelligence. Key challenges are identified: infrastructure requirements, dependence on foreign technology, ethical concerns including data bias, and transparency in AI-driven decisions. A comprehensive policy framework is proposed, emphasizing strategic partnerships, robust data governance, and ethical guidelines to mitigate risks and maximize AI’s benefits. The discussion highlights the crucial need for AI-specific hardware investment, including microchips and supercomputing infrastructure, while advocating for fostering local expertise and reducing reliance on external providers. The paper argues that AI empowers Indonesia to enhance military capabilities, strengthen cyber defenses, and optimize strategic decision-making. However, a balanced approach that prioritizes ethical considerations, transparency, and a clearly defined command chain is crucial for responsible AI deployment. This research serves as a roadmap for Indonesian policymakers to navigate the complex landscape of AI in national defense, ensuring sovereignty, security, and ethical alignment in the digital age. The implementation of AI is not just an option but a strategic imperative.